2017
DOI: 10.1002/ceat.201600322
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Separation of Different‐Shape Particles Using a Mini‐Hydrocyclone

Abstract: The separation efficiency from water of different-shape particles was studied experimentally using a mini-hydrocyclone. Spherical and flaky (plate-like) aluminum particles with the same particle size distributions were employed. Also, the effects of the feed flow rate and the temperature on the separation performance were studied. The results were investigated in terms of slurry recovery, total efficiency, and partition curves. The separation efficiency of the spherical particles increased with increasing part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Particle classification using mini-hydrocyclones has been the focus of some experimental studies. Abdollahzadeh et al [7] showed that the classification efficiency in a 15mm hydrocyclone improves at low feed concentrations and high velocities, which is in agreement with the findings of Niazi et al [2].…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Particle classification using mini-hydrocyclones has been the focus of some experimental studies. Abdollahzadeh et al [7] showed that the classification efficiency in a 15mm hydrocyclone improves at low feed concentrations and high velocities, which is in agreement with the findings of Niazi et al [2].…”
Section: Introductionsupporting
confidence: 84%
“…the fraction of particles that reports to the underflow without classification, is normally equal to the water recovery. However, unlike large hydrocyclones, mini-hydrocyclones exhibit considerably larger bypass than the water recovery [1,2,3,4]. This large bypass makes mini-hydrocyclones ideal for dewatering applications but poses a disadvantage for classification due to the amount of misplaced particles go-2 ing to the underflow.…”
Section: Introductionmentioning
confidence: 99%
“…Several parameters affect the performance of hydrocyclones, including the inlet velocity, solid content, liquid-phase viscosity, particle size and shape, and so forth. Saber et al [20] believed that the separation effect would improve with the increase in the size of spherical particles, which was obviously better than that of plate-like particles. Also, the separation effect declined with the increase in the size of plate-like particles with diameters more than 60 µm.…”
Section: Influence Of Maximum Projected Area and Volume Changes On Sementioning
confidence: 99%
“…Note here that our review focuses on micro-/nanoscale separations of rigid particles in liquid phases. Therefore, we exclude shape-separation processes of powders or particles with larger than microscale size (>10 μm), such as microsieves (Furuuchi et al, 1993), cyclones (Niazi et al, 2017), and other powder separation processes (Furuuchi and Gotoh, 1992). Approaches with differential mobility analyzers (Beranek et al, 2012), where particles are dispersed in a gas phase, are also excluded.…”
Section: Introductionmentioning
confidence: 99%